Army Biometric Applications Identifying and Addressing Sociocultural Concerns - Woodward, John D. (RAND Corporation, 2001)
Every human possesses more than one virtually infallible form of identification. Known as biometrics, examples include fingerprints, iris and retinal scans, hand geometry, and other measures of physical characteristics and personal traits. Advances in computers and related technologies have made this a highly automated process through which recognition occurs almost instantaneously. With concern about its information assurance systems and physical access control increasing, the Army has undertaken an assessment of how it can use biometrics to improve security, efficiency, and convenience. This report examines the sociocultural concerns that arise among soldiers, civilian employees, and the general public when the military mandates widespread use of biometrics. The authors see no significant legal obstacles to Army use of biometrics but recommend that the Army go beyond the provisions of the Privacy Act of 1974 to allay concerns related to this emerging technology. This report should be of interest to those responsible for access control as well as anyone concerned about privacy and technology issues.